Numerical study on the summertime patches of red tide in the adjacent sea of the Changjiang (Yangtze) River Estuary, China. (June 2019) - Qu, Dapeng; Yu, Huaming; Sun, Yuchen; Zhao, Yunxia; Wei, Qinsheng; Yu, Haiqing; Kelly, Ryan M.; Yuan, Yeli
Abstract: High incident rates of red tide have occurred off the coast of the Changjiang (Yangtze) River Estuary in summer, resulting from a magnified population growth discharging substantial nutrient loads into this vicinity. The presence of elevated Chlorophyll-a concentrations (≥36.3 μg/l), low suspended sediment concentrations in surface and mid-layers (<10 mg/l), a strong saline front and surface water temperature gradient, veering surface winds, and a bimodal shape to the Changjiang Diluted Water (CDW) revealed two red tide patches appearing between August 6–13, 2010. Two distinguishable hydrodynamic driving mechanisms, connected to these incidents, are diagnosed. Field observations and numerical simulations determined a red tide patch in the northeastern offshore area is caused by a northeast transport of the CDW truncated by a northwest intrusion of the Taiwan Warm Current (TWC) as winds deviated. Red tide occurrence in the southern nearshore area originated from a plume front where CDW interfaces with the TWC. Highlights: Hydrodynamic environment variability determines the pattern of red tide incidents. Southeast winds >8 m/s correlates with detachment event's timing and red tide events. Plume front created by current mixing and presence of coastal upwelling region. Light intensity and nutrient loads yield chlorophyll- a concentrations to >20 μg/l.